Banking System Fragility : Likelihood Versus Timing of Failure; An Application to the Mexican Financial Crisis - Billings, Robert (IMF Working Papers; Working Paper ;, 1996)
This paper tests empirically the proposition that bank fragility is determined by bank-specific factors, macroeconomic conditions and potential contagion effects. The methodology allows for the variables that determine bank failure to differ from those that influence banks' time to failure (or survival rate). Based on the indicators of fragility of individual banks, we construct an index of fragility for the banking system. The framework is applied to the Mexican financial crisis beginning in 1994. In the case of Mexico, bank-specific variables as well as contagion effects explain the likelihood of bank failure, while macroeconomic variables largely determine the timing of failure.